Ligth shelt: estudo da sua eficiência lumínica através de simulação computacional - Castro, Eduardo Breviglieri Pereira de (1996)
Undoubtly, the imense majority of buildings have their enclosures illuminated through vertical openings in their facades, known as "windows". An analysis of these windows, show us a series of caracteristics present in all situations, many of that very unfavorable related to its utilization as light sources for inner spaces. One of these caracteristics, is the enormous diference between ilumination levels near the apertures and deeper in the room illuminated by that aperture, i.e., the poor natural light distribution in a longitudinal section of that room. However, there are many architectural elements w hich can be used to improve this natural Iight distribution. This is exactly the case of a "lightshelf', which demonstrates a proved eficiency in direct insolation protection anel natural light redistribution in building interiors. So, it is very important to study this element and to the develop tools to calculate its effects in the early phases of the architectural process, which is of great interest to architects anel engineers. This work tries to colaborate in the solution of this problem, presenting a microcomputer simulation program which allows the user compare resulting illuminating levels in a roam lightned through an exterior vertical window, with anel without the presence of a lightshelf, and visualize the results in a numerically and grafically way. So, helping to measure in a cienbfically way, the eficiency of this so far subutilizecl element in our archictectural production.